1997
DOI: 10.1002/(sici)1096-987x(19970130)18:2<221::aid-jcc7>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

A molecular mechanics force field for NAD+ NADH, and the pyrophosphate groups of nucleotides

Abstract: Empirical force field parameters for nicotinamide (NIC+) and 1,4‐dihydronicotinamide (NICH) were developed for use in modeling of the coenzymes nicotinamide adenine dinucleotide (NAD+) and NAD hydride (NADH). The parametrization follows the methodology used in the development of the CHARMM22 all‐hydrogen parameters for proteins, nucleic acids, and lipids. Parametrization of inorganic phosphate for use in adenosine di‐ and triphosphates (e.g., ADP and ATP) is also presented. While high level ab initio data, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
195
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(201 citation statements)
references
References 20 publications
5
195
0
1
Order By: Relevance
“…Figure 1 shows the results obtained for the first MD simulation in which the published NADH parameters of Pavelites et al 18 were employed. These show reasonably good agreement with the experimental spectra considering that the assumption of linear response is being used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows the results obtained for the first MD simulation in which the published NADH parameters of Pavelites et al 18 were employed. These show reasonably good agreement with the experimental spectra considering that the assumption of linear response is being used.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for doing this was to investigate how sensitive our method was to the quality of the molecular dynamics parameters. The method detailed above resulted in a force field that, while reasonably good, was not strictly parametrized in the thorough method employed by Pavelites et al 18 The variation between the second and third simulations concerned the parametrization of the amide moiety of the NADH cofactor (atoms N7, O14, C18, H67, and H73, Appendix A, Table 4). Trial calculations showed that the molecular orbitals involved in the excitation corresponding to NADH absorption and emission are highly dependent on the structure of this amide group.…”
Section: Methodsologymentioning
confidence: 99%
See 1 more Smart Citation
“…CHARMM27 protein (33) and CHARMM36 lipid (34) force fields were used. The force field for ATP was from Pavelites et al (35).…”
Section: Methodsmentioning
confidence: 99%
“…Maestro Molecular Modeling software was used to build the acyl chain for the phosphopantetheine moiety. Force field parameters were the ff99 set for proteins (43) and published parameters (44,45) for NADH. The Amber antechamber module and GAFF force field (46) with am1bcc charges (47) were used to generate the parameters for phosphopantetheine and the attached acyl chain.…”
Section: Methodsmentioning
confidence: 99%